Modeling a Solution for Smart Space Planning Aiming for Energy Efficiency in Industry 4.0 - Viviane Bessa Ferreira; Raphael de Aquino Gomes; Wesley Pacheco Calixto (The Journal of Engineering and Exact Sciences)
The escalating demand for energy in the industrial sector poses significant challenges, necessitating the exploration of innovative solutions. In response, there is a growing inclination towards leveraging the transformative potential of Industry 4.0 technologies to enhance energy efficiency in these spaces. The integration of smart technologies emerges as a promising alternative, prompting a critical examination of how computing resources, equipment, and components can be strategically arranged within these environments. Addressing this imperative, the present study endeavors to contribute to the discourse by proposing a comprehensive solution for the design and planning of smart spaces, grounded in Industry 4.0 technologies, with a specific focus on achieving energy efficiency. The research not only conceptualizes the proposed model but also provides insights into its preliminary implementation, thereby bridging the gap between theoretical considerations and practical applications in the pursuit of sustainable and intelligent industrial spaces.